The Impact of Social Media on Employee Work Performance with Trust as a Mediation Variable - Nilasari, B. Medina (Jurnal Manajemen, 2020)
Can the use of social media which is currently a trend in the community, have an influence on improving employee performance? This is what makes the research carried out. The analysis technique used is the Structural Equation Model (SEM) method with AMOS version 23. The sample consisted of 102 people who were employees in various types of private companies in DKI Jakarta. The results showed that the more social media is used to communicate with colleagues in completing work, the more trust among employee increases. Also the more social media is used to communicate with colleagues in completing work, the more improves employee work performance. But trust can not influence performance of employee, and trust is not a variable that mediates between social media and employee performance.